Efficacy of bioagents against root rot disease of groundnut caused by Macrophomina phaseolina - Godara, S L; Kumar, Suresh (Indian Journal of Plant Protection, 2020)
Efficacy of selected bioagents like Trichoderma harzianum, T.viride and Pseudomonas fluorescens were evaluated used as alone or with different combinations as seed treatment and soil application along with or without FYM were against root rot disease of groundnut caused by Macrophomina phaseolina under field conditions during kharif -2013 and 2014. Among all the treatments T4 (T. viride + P. fluorescens used as seed treatment at 4+4 gm/kg seed and soil application at 2.5+2.5 kg/ha. along with FYM) resulted minimum disease incidence (9.08%) and highest per cent disease control (72.96%) followed by the treatment T3(T. viride + P. fluorescens used as seed treatment (4+4 gm/kg seed). This treatment was also found effective on the development of total number of pods per plant. The root, shoot lengths and yield were significantly increased in response to combined bioagent treatments. Highest root, shoot lengths and seed yield were recorded in the treatment T4 which was closely followed by T3. Whereas, rest of the treatments found least effective on root, shoot length and seed yield of the groundnut plants.